Genetic mapping of expressed sequence tag polymorphism (ESTP)markers in loblolly pine (Pinus taeda L.) - Temesgen, B.; Brown, G.R.; Harry, D.E.; Kinlaw, C.S.; Sewell, M.M.; Neale, D.B.
Abstract The development and mapping of genetic markers based upon expressed sequence tag polymorphisms (ESTPs)in loblolly pine (Pinus taeda L.)are reported. The new markers were generated by PCR-amplification of loblolly pine genomic DNAs with primers designed from sequenced cDNAs. The cDNA libraries were constructed from RNAs expressed in the needles of loblolly pine seedlings or in the xylem from young trees. DNA polymorphisms were identified by analyzing the amplified products for differences in fragment size or restriction sites, or by examining mobility differences using denaturing gradient gel electrophoresis (DGGE). DGGE revealed more DNA polymorphisms than the other two methods. Fifty six ESTPs were mapped using either of two mapping populations and positioned onto a loblolly pine consensus genetic map. Unlike many other markers commonly used in forestry, ESTPs can be used as orthologous markers for comparative mapping, to map genes of known function, or to identify candidate genes affecting important traits in loblolly pine.
Keywords: DENATURING GRADIENT GEL ELECTROPHORESIS (DGGE); GENETIC MARKER; GENETIC LINKAGE MAP; LOBLOLLY PINE ( PINUS TAEDA L.)